Political feasibility of 1.5°C societal transformations: the role of social justice - Patterson, James J; Thaler, Thomas; Hoffmann, Matthew; Hughes, Sara; Oels, Angela; Chu, Eric; Mert, Aysem; Huitema, Dave; Burch, Sarah; Jordan, Andy (Elsevier, 2018)
Constraining global climate change to 1.5°C is commonly understood to require urgent and deep societal transformations. Yet such transformations are not always viewed as politically feasible; finding ways to enhance the political feasibility of ambitious decarbonization trajectories is needed. This paper reviews the role of social justice as an organizing principle for politically feasible 1.5°C transformations. A social justice lens usefully focuses attention on first, protecting vulnerable people from climate change impacts, second, protecting people from disruptions of transformation, and finally, enhancing the process of envisioning and implementing an equitable post-carbon society. However, justice-focused arguments could also have unintended consequences, such as being deployed against climate action. Hence proactively engaging with social justice is critical in navigating 1.5°C societal transformations.